Quantitative Analysis of Group Cohesion Impact on Organizational Commitment: Analisis Kuantitatif Dampak Kohesi Kelompok terhadap Komitmen Organisasi - Maryam, Effy Wardati; Rifdayanti, Novia (Journal of Islamic and Muhammadiyah Studies, 2024)
This study investigates the relationship between group cohesiveness and organizational commitment among members of the Muhammadiyah Student Association (IMM) at Muhammadiyah University of Sidoarjo. The motivation stems from challenges related to inconsistent task completion leading to member attrition. Using a quantitative correlational approach, the study aims to address a knowledge gap regarding the association between these variables. The research sample includes 180 IMM UMSIDA members, with data collected through established scales for group cohesiveness and organizational commitment. Analysis employs Spearman's rho product moment correlation test. Findings reveal a significant positive correlation (rxy = 0.560, p < 0.05) between group cohesiveness and organizational commitment, indicating higher group cohesiveness correlates with greater organizational commitment. Group cohesiveness accounts for 29.8% of organizational commitment variance, suggesting other factors contribute to the remaining 70.2%. Limitations include single-variable focus and reliance on correlational methodology. The study underscores the importance of fostering group cohesiveness within student organizations to enhance organizational commitment. Future research should explore additional variables and expand population demographics to enrich understanding and implications for organizational dynamics. Highlight: Positive Correlation: Group cohesiveness positively relates to organizational commitment. Sample Size: Research includes 180 members of IMM UMSIDA, providing robust data. Practical Implications: Findings suggest fostering group cohesion enhances organizational commitment. Keywoard: Group Cohesiveness, Organizational Commitment, Student Organizations, Quantitative Correlation, Muhammadiyah University